2015
DOI: 10.1111/pai.12395
|View full text |Cite
|
Sign up to set email alerts
|

Asthma control in children is associated with nasal symptoms, obesity, and health insurance: a nationwide survey

Abstract: Half of the children with asthma were poorly controlled. Nasal symptoms and obesity are important determinants of asthma control. Children without health insurance are at greater risk of poor asthma outcomes; this association is reported for the first time in a European country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Several risk factors for uncontrolled pediatric asthma have been shown in a population‐based Web survey, such as low birthweight, obesity, pet ownership before birth, and allergic comorbidities (especially AR) . Children with uncontrolled asthma present AR and obesity in half of the cases . It is debated whether systemic obesity‐associated inflammation may modulate airway diseases.…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…Several risk factors for uncontrolled pediatric asthma have been shown in a population‐based Web survey, such as low birthweight, obesity, pet ownership before birth, and allergic comorbidities (especially AR) . Children with uncontrolled asthma present AR and obesity in half of the cases . It is debated whether systemic obesity‐associated inflammation may modulate airway diseases.…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…Being overweight/obese is a risk factor for having non-controlled asthma [32]. Neck circumference is reported by Maltz et al as being associated with asthma control and quality of life in males [33].…”
Section: Asthma Control and Severitymentioning
confidence: 99%
“…Considering a hypothetic scenario (data not shown) in which all Portuguese children with asthma were controlled, the savings would be more than 30,000,000 € per year (20% reduction). As previously reported, children with not controlled asthma had significantly more unscheduled medical visits and hospitalisations (10,24); knowing that uncontrolled asthma is, also, the major determinant for higher costs, effective policies should be directed to improve asthma control and reduce acute care medical visits. Other studies showed that asthma plans/interventions can reduce symptoms, reduce healthcare services use and be cost-effective (25,26).…”
Section: Determinants Of Cost Variation In Childhood Asthmamentioning
confidence: 73%
“…Reducing acute asthma care costs should be one of the major targets for potential savings. Also, by reducing it, other domains (e. g., indirect costs) could also be lowered as poor controlled asthma is associated to higher unscheduled medical visits and higher costs of lost work (10,23).…”
Section: Previously Published Studies Reported Proportions Of Direct mentioning
confidence: 99%